2017
DOI: 10.3389/fnmol.2017.00181
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Kv7/M Potassium Channels in Controlling Ectopic Firing in Nociceptors

Abstract: Peripheral nociceptive neurons encode and convey injury-inducing stimuli toward the central nervous system. In normal conditions, tight control of nociceptive resting potential prevents their spontaneous activation. However, in many pathological conditions the control of membrane potential is disrupted, leading to ectopic, stimulus-unrelated firing of nociceptive neurons, which is correlated to spontaneous pain. We have investigated the role of KV7/M channels in stabilizing membrane potential and impeding spon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 88 publications
2
52
0
Order By: Relevance
“…In fact, we found that XE991 caused a slight increase in AP threshold and had a tendency to reduce AP discharge at nodose C-fiber terminals in the lungs. These observations are at odds with the repetitive AP firing induced by focal puff application of XE991 in rat lumbar DRG neurons (51) and with the finding that XE991 modestly increased afferent firing in response to noxious bowel distension in mouse distal colons (17). However, the absence of effects on AP firing properties in mouse sympathetic neurons (52) and an increase in the pressure threshold for rat baroreceptor discharge (16) by XE991 have also been reported.…”
Section: Discussionmentioning
confidence: 94%
“…In fact, we found that XE991 caused a slight increase in AP threshold and had a tendency to reduce AP discharge at nodose C-fiber terminals in the lungs. These observations are at odds with the repetitive AP firing induced by focal puff application of XE991 in rat lumbar DRG neurons (51) and with the finding that XE991 modestly increased afferent firing in response to noxious bowel distension in mouse distal colons (17). However, the absence of effects on AP firing properties in mouse sympathetic neurons (52) and an increase in the pressure threshold for rat baroreceptor discharge (16) by XE991 have also been reported.…”
Section: Discussionmentioning
confidence: 94%
“…A recent computational study provided a biophysical foundation to these and similar observations by utilizing a multi‐component model of rat C fibre that included a geometrically realistic nociceptive nerve ending in the skin (Barkai et al, ). When sufficiently pronounced, M channel inhibition resulted in ‘spontaneous firing’.…”
Section: Channels and Peripheral Fibre Excitability In Vitro In Simentioning
confidence: 99%
“…For the "realistic" type of the terminal tree, which was reconstructed according to one of our arbitrary experimental observations (Barkai et al, 2017), the distal axon ending tapered at its end and expanded into a terminal tree composed of 27 branches. For proper electrical propagation from the terminal tree to the peripheral axon, these two compartments were connected by a tapered cone-like axon with a linearly changing diameter over 100 µm of length.…”
Section: Terminal Tree Structuresmentioning
confidence: 99%
“…The model neuron of all tree structures includes the following Hodgkin-Huxley-type ion channels used in Barkai et al (Barkai et al, 2017) and Goldstein et al (Goldstein et al, 2019):…”
Section: Active Conductancesmentioning
confidence: 99%
See 1 more Smart Citation